THE CONFORMITY OF LAW NO 32 OF 2014 WITH THE ISLAMIC PRINCIPLES ON THE MARINE NATURAL RESOURCES MANAGEMENT AND PROTECTION. - Murdian (FH 16 UMY 105, 2016)
Indonesia as the largest archipelago country in the world with two thirds of its area is the ocean, is the gift of God that abundant natural resources of the sea in the form of potential fisheries, mining of minerals and energy, transportation and excursions sea nautical invaluable which should be maintained and managed properly in accordance with the constitutional mandate to realize the prosperity of all the people of Indonesia. Alas, the fact remains that the habitat of the coastal ecosystems and sea Indonesia increasingly damaged, natural wealth exploited sea is excessive and unsustainable, as well as illegal fishing is lively going on. This paper seeks to elaborate on and analyse the conformity of legislation no. 32 of 2014 about marine by Islamic principles in the management and protection of natural resources of the sea. hopefully this effort can create the marine management and protection natural resources sustainably and optimal. Accordingly, the marine sector will provide the benefit for all the people of Indonesia, both for the present generation and future generation as mandated by the 1945 Constitution. This paper is the result of the study of normative law, the study of librarianship that uses descriptive comparative approach. This research concludes that the confirmites among of them in the terms of: 1. The Principle of the Godhead. 2. The is a Caliphate or Khalifah (the Principle of God's Representative) and Amanah (Trust Principle of God). 3. Useful Creation/Istishlah (The Principle of Benefit) and Ecological Balance/I'tidal (The Principles of Ecological Balance). 4. Inter-generational Equity/Sustainable Use (The Principle of Sustainability). 5. The principle of the Government is authorized to regulate and enforce the law (ta'zir). Key words: Tawhidic, khalifah, amanah, istishlah, i'tidal, inter-generational equity, sustainable use, prohibition of excessive use of natural resources, ta'zir.